Immovable Truth: Divine Knowledge and the Bible at the University of Vienna (1384-1419) - Lukács, Edit Anna , author.
1 online resource (240 pages)
Keywords: In the 14th century, hypotheses about a lying God, deceived Christ, and the changeability of the past circulated. At the new University of Vienna, three German masters attempted in their lectures on the Old Testament to counter them. Their commentaries are the longest, the most influential, and perhaps even the most inspiring commentaries on the Bible written at Vienna. This book offers a glimpse into their most unusual ideas, apocalyptic expectations, heretics, toads, and devils; assessments of Amalric of Bena, Moshe Taku, and Petrarch; and, last, but not least, the search for an immovable truth that fills their pages.